Tahap Penguasaan Kemahiran Generik Dalam Kalangan Pelajar Tahun Akhir Diploma Kejuruteraan Elektrik Serta Pendidikan, UTHM - Musa, Marliana; Esa, Ahmad (Journal of Techno-Social, 2009)
Generic skill is very important especially in the globalization era. Dominating this skill will give an advantage especially to students who are going to involve in working field. This research was conducted to determine student’s awareness level on the importance of generic skill, and the effective teaching and learning methods to improve generic skill acquisition based on student’s perception. 42 students of Diploma in Electrical Engineering with Education from Faculty of Electrical and Electronic Engineering, UTHM get involved in this research emprising 25 male and 17 female students. The instrument used in this research is a set of questionnaire. The data were processed through Statistic Package for Social Science (SPSS) version 11.0.There were adopted the analysis descriptive statistics technique using score mean, percentage and standard deviation. The research finding showed level of awareness on theimportance of generic skills among final year student of Diploma in Electrical Engineering with Education’s is at high level. Beside that, based on student’s perception, an effectiveness of teaching and learning methods is problem based-learning.